An Investigation of Potential Health Risks from Zoonotic Bacterial Pathogens Associated with Farm Rats - Lorina Badger-Emeka; Yasmeen Al-Mulhim; Fatimah Al-Muyidi; Maram Busuhail; Salma Alkhalifah; Norah AlEid (SAGE Publishing, 2020)
Background: The 21st century has seen a wide range of diseases resulting from zoonotic infections, of which bacterial infections have led to outbreaks of food-borne diseases. Aim: The study looks at bacterial pathogen carriage by farm rats and their antimicrobial susceptibility, with the view of providing insights for antimicrobial surveillance. Method: Farm rats of Rattus rattus species where randomly collected alive from farms in Al-Ahsa using food baits. They were anaesthetize with urethane within 4 h of collection and were unconscious for the collection of samples. Basic bacteriological culturing methods were used for culturing of bacterial isolates on selective media while the Vitek 2 compact automated system (BioMerieux, Marcy L'Etoile, France) was used for bacteria identification and antimicrobial susceptibility test. Obtained data were analysed using chi-square and paired t -test with significant difference between sensitive and resistance to antimicrobial susceptibility taken at P  < .05. Results: Isolated Gramme-negative pathogenic bacteria included strains of Escherichia coli, Pseudomonas oryzihabitans , strains of Pseudomonas aeruginosa , and Salmonella. For the Gramme-positive bacteria, 4 strains of Staphylococcus aureus were encountered. Other Gramme-positive bacteria were coagulase-negative Staphylococcal species (CoNS) as well as Staphylococcus lugdunensis . There was a 100% resistance to the penicillins and a high resistance to imipenem (71%) by the Staphylococcal isolates. Resistance was also high against the β-lactams by the Gramme-positive bacteria isolates. For the Gramme-negative bacteria, there was a higher than 50% resistance by the isolates against the following antibiotics: ampicillin (78%), amoxicillin/clavulanic acid (67%), cefotaxime (77%), ceftazidime (67%), cefepime (78%), norfloxacin (67%), nitrofurantoin (67%), and trimethoprim/sulfamethoxazole (78%). Conclusion: The results showed high antimicrobial resistance that will need monitoring for control of spread from farm rats to humans.